Greenness and chronic respiratory health issues: a systematic review and meta-analysis - Tang, Mingcheng; Liu, Wei; Li, Haifang; Li, Fengyi (Frontiers in Public Health, 2023)
Introduction The number of chronic respiratory disease (CRD) individuals worldwide has been continuously increasing. Numerous studies have shown that greenness can improve chronic respiratory health issues through different mechanisms, with inconsistent evidence. By quantitatively summarizing existing studies, our purpose is to determine the connection between greenness exposure and various chronic respiratory health. Methods We conducted a comprehensive search on PubMed, EMBASE, and Web of Science core databases to identify relevant studies on the correlation between greenness exposure and chronic respiratory health issues. Studies published up to January 2023 were included in the search. The study used the most frequent indicator (normalized difference vegetation index [NDVI]) as the definition of greenness exposure. Results We finally identified 35 studies for meta-analysis. We calculated pooled effects across studies using a random-effects model and conducted a subgroup analysis by age and buffer zones to discuss the effects on chronic respiratory health issues. This study showed that 0.1 increments in NDVI were significantly related to lower rates of asthma incidence, lung cancer incidence, and chronic obstructive pulmonary disease (COPD) mortality risk; the pooled RRs were 0.92 (95% CI: 0.85–0.98), 0.62 (95% CI: 0.40–0.95), and 0.95 (95% CI: 0.92– 0.99), respectively. For the age subgroup, the higher greenness exposure level was related to the incidence rate of asthma among teenagers aged 13–18years (RR: 0.91; 95% CI: 0.83–0.99). For the buffer subgroup, a positive relationship with greenness exposure and asthma incidence/prevalence at 200–300m and 800– 1000m buffers, as well as the COPD mortality at 800–1000m buffer, the pooled RRs were 0.92 (95% CI: 0.86–0.98), 0.87 (95% CI: 0.81–0.93), and 0.93 (95% CI: 0.88– 0.98), respectively. Evidence of publication bias was not detected in this study. Discussion Our study is the first global meta-analysis between greenness and various CRDs to report an inverse association. Further research is needed in order to determine the effect of greenness exposure on different CRDs. Therefore, when planning for green development, more consideration must be given to public health and green management as intervention measures. https://www.crd.york.ac.uk/PROSPEROFILES/384029_STRATEGY_20230116.pdf